Analysis of Genetic Variations in Connexin 26 (GJB2) Gene among Nonsyndromic Hearing Impairment: Familial Study - Smita Hegde; Rajat Hegde; Suyamindra S. Kulkarni; Kusal K. Das; Pramod B. Gai; Rudragouda S. Bulagouda (Global Medical Genetics, 2022)
Objective The goal of this research was to investigate the gap junction beta 2 (GJB2) gene mutations associated with nonsyndromic hearing loss individuals in North Karnataka, India. Materials and Methods For this study, patients with sensorineural genetic hearing abnormalities and a family history of deafness were included. A total of 35 patients from 20 families have been included in the study. The patient's DNA was isolated from peripheral blood samples. The GJB2 gene coding region was analyzed through Sanger sequencing. Results There is no changes in the first exon of the GJB2 gene. Nine different variants were recorded in second exon of the targeted gene. W24X and W77X are two nonsense mutations and three polymorphisms viz. R127H, V153I, and I33T were reported along with four 3′-UTR variants. A total (9/20) of 45% of families have been identified with mutations in the targeted gene. Conclusion GJB2 mutations were identified in 19 deaf-mute patients (19/35), and 13 patients were homozygous for the mutations identified in our study cohort. In our study, W24X mutation was found to be the pathogenic with a high percentage, prompting further evaluation of the other genes, along with the study of additional genetic or external causes in the families, which is essential.